معدل انتشار إكزمة اليد بين المرضى المراجعين للعيادة الجلدية والتناسلية في مستشفى الأسد الجامعي باللاذقية - معلا محمد (Latakia University Journal -Medical Sciences Series, 2019)
إكزمة اليد مرض شائع. تشكل إكزمة اليد مشكلة حقيقية عند بعض المرضى . أسباب إكزمة اليد عديدة: خارجية وداخلية. أجريت هذه الدراسة الحالية لإعطاء فكرة عن معدل انتشار إكزمة اليد. شملت الدراسة 6448 مريض راجعوا العيادة الجلدية في مستشفى الأسد الجامعي باللاذقية على مدى عام. كانت نسبة إكزمة اليد بين هؤلاء المرضى 9.24% . قمنا بدراسة نسبة توزع إكزمة اليد حسب : نمط الإكزمة، عمر المرضى، الجنس، والمهنة. كما درس تأثير التغيرات الفصلية على معدل الإصابة بإكزمة اليد . أظهرت الدراسة نسبة عالية لإكزما التماس، خاصة عند الإناث. أكدت دراستنا أن للتغيرات الفصلية والعوامل المهنية تأثير على معدل انتشار إكزمة اليد. Hand eczema is a common disease that poses a real problem for some patients. The causes of hand eczema can be either exogenous or endogenous. This study is carried out to give an idea about the prevalence of hand eczema. It involves 6448 outpatients who are admitted over one year to the skin clinic at Al-Assad University Hospital, Lattakia, Syria. The ratio of hand eczema among those outpatients is 9.42%. We have studied the prevalence of hand eczema according to the type of eczema, patient’s sex, and occupation. We have also studied the effect of seasonal changes on this ratio. The study has shown high incidence of contact dermatitis, especially in females. Our study has suggested that seasonal changes and occupations have influenced the prevalence of hand eczema.